Cargasus the flying carabao - Alaurin, Edgardo Delgado Father, O.P. (España, Manila, Philippines University of Santo Tomas Publishing House, 2020)
World-building is one very important convention of fantasy adventure and the author succeeds in construction a realm that is other-worldly yet also familiar, believable, and very close to home since the writer's sensibility is very Filipino.

You will love the lead characters because they exemplify both virtue and valor while the villains serve as perfect foils of the protagonists. As a Catholic writer, Fr. Alaurin discourses on the concept of the good being rewarded, the evil left unpunished, eventually forgiven and transformed for the better, but he does it with such subtlety and flair.

Readers will surely delight in this fantasy adventure because it has all the elements of an interesting and entertaining novel: love, romance, drama, action, suspense, conflict, humor, and of course a happy ending that gives a hint that there might be a continuation to look forward to.
Chapter 1: The Origin -- Chapter 2: The Ninth Month, the Beginning -- Chapter 3: The Homecoming -- Chapter 4: Tracing the Trail Back -- Chapter 5: The Tale of the Accursed -- Chapter 6: The New Catch -- Chapter 7: New Beginnings -- Chapter 8: The Early Years -- Chapter 9: Two Visions -- Chapter 10: Hostile Visitors -- Chapter 11: The View from the Top -- Chapter 12: The Entertainment -- Chapter 13: The Rescue -- Chapter 14: Rebuilding and Recovering -- Chapter 15: Angelic Signs -- Chapter 16: The Long Flight -- Chapter 17: Sailing the Open Sea -- Chapter 18: The Hustlers -- Chapter 19: Pintados of Pan-ay -- Chapter 20: The Princess of Palaw-an -- Chapter 21: The First Contest -- Chapter 22: The Second Contest -- Chapter 23: The FLoating Gentle Giant -- Chapter 24: The News that Said it all! -- Chapter 25: The Reunion and Tales to Tell -- Chapter 26: Scores to Settle -- Chapter 27: "Datu Maguilas" -- Chapter 28: Up Above Close and Personal -- Chapter 29: The Struggle for the Mutya -- Chapter 30: Turn of Events -- Chapter 31: The Last Mission -- Chapter 32: Down to Sulukas -- Chapter 33: The Ordeal of Aswud -- Chapter 34: Back to the Surface -- Chapter 35: The Dilemma -- Chapter 36: The Wedding.
"Published with permission from the Dominican Province of the Philippines, Reg. II p. 76, Prot. No. 01-197605/109."--Title page verso.
Keywords: Fantasy fiction, Philippine (English); Water buffalo -- Philippines -- Fiction